Initial Experiences with the MitraClip G4: Review of the Novel Device Features. Issue 5 (September 2021) - Ives, Christopher W.; Prejean, Shane P.; Vardas, Panos N.; Von Mering, Gregory; Ahmed, Mustafa I.
Objective: Percutaneous edge-to-edge mitral valve repair is an evolving procedure with increasing indications for use. The MitraClip™ G4 is the newest device with 4 device options, each with distinct characteristics. While the NTR and XTR clips have been in use, the G4 adds 2 new wider clips with additional features, the NTW and XTW. Methods: We reviewed 26 cases employing the MitraClip G4 at our institution from November 2019 to March 2020. Results: The NTR, XTR, NTW, and XTW clips were used in 3 (11.5%), 0 (0.0%), 16 (61.5%), and 11 (42.3%) cases, respectively. Median mitral regurgitation grade was reduced from 4+ to 1+, though 7 (27%) cases had 2+ residual mitral regurgitation. Conclusions: The new G4 device includes simplified instructions for use, the option of a wider clip, controlled gripper actuation, and potential left atrial pressure monitoring. The newest MitraClip G4 device allows for potential improved treatment options for patients with mitral regurgitation.